Effect of Li and Bi co-doping and sintering temperature on dielectric properties of PLZT 9/65/35 ceramics. Issue 5 (1st April 2017) - Limpichaipanit, Apichart; Ngamjarurojana, Athipong
Abstract: In the present study, lead-lanthanum-zirconate-titanate (PLZT) ceramics were prepared by a solid-state mixed oxide method. Different amount of lithium carbonate and bismuth oxide (0.15 mol%, 0.45 mol% and 0.75 mol%), where the ratio of Li:Bi =1:1 by mole, was added to PLZT to investigate the effect of Li and Bi co-doping. The ceramic samples were sintered at the temperatures of 1000, 1050, 1100, 1150 and 1200 °C for 4 h. After that, all samples were subjected to phase identification, physical property determination (sintered density and microstructure) and dielectric property measurement. It was found that doping of 0.15 mol% Li and Bi resulted in maximum dielectric constant (εr =7819) when sintered at 1200 °C. Grain size of PLZT ceramics was dependent on sintering temperature and dielectric properties were affected by the chemical composition rather than the grain size of the ceramics. Therefore, co-doping of Li and Bi was useful as it could improve the dielectric properties of PLZT ceramics.